2019
DOI: 10.1002/admi.201900411
|View full text |Cite
|
Sign up to set email alerts
|

AFM Study of pH‐Dependent Adhesion of Single Protein to TiO2 Surface

Abstract: The effect of pH‐induced electrostatic conditions on the molecular interaction force of a single lysozyme molecule with TiO2 is investigated using atomic force microscopy (AFM). The force between the charged or neutral lysozyme molecule and the TiO2 surface is measured at different pH from 3.6 to 10.8. It is found to be directly proportional to the contact area, given by an effective diameter of the lysozyme molecule, and is further qualitatively verified by the AFM‐measured friction coefficients. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Intrinsically, the SERS intensity is strongly related to the interactions among the adsorbed molecules and their electron-transfer ability, implying that regulating them is essential to improve the enhancement and to lower the limit of detection. To enhance the sensitivity in SERS-based bioanalysis and biodetection, not only the choice of the substrates, but also the environmental conditions, such as pH, , temperature, , and ionic strength, , can be used to effectively modify the interaction strength of the adsorbed proteins, leading to an important enhancement of sensitivity . However, only a handful investigations have been conducted on how to adjust the environmental effects, i.e., pH, temperature, ionic strength, to increase the electron transfer ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrinsically, the SERS intensity is strongly related to the interactions among the adsorbed molecules and their electron-transfer ability, implying that regulating them is essential to improve the enhancement and to lower the limit of detection. To enhance the sensitivity in SERS-based bioanalysis and biodetection, not only the choice of the substrates, but also the environmental conditions, such as pH, , temperature, , and ionic strength, , can be used to effectively modify the interaction strength of the adsorbed proteins, leading to an important enhancement of sensitivity . However, only a handful investigations have been conducted on how to adjust the environmental effects, i.e., pH, temperature, ionic strength, to increase the electron transfer ability.…”
Section: Introductionmentioning
confidence: 99%
“…It implies that the measurements at the microscale are critically needed. In our previous work, based on the atomic force microscopy (AFM), a method was proposed to determine the molecular force between the protein molecules and different TiO 2 surfaces. , However, applying this method to capture the interactions and to understand the SERS mechanism at the molecular level has not yet been carried out. Meanwhile, the enhancement factor (EF) is an essential parameter and key index in the field of SERS.…”
Section: Introductionmentioning
confidence: 99%
“…When the protein molecules are in the solution, the effective molecular size, that is, hydrodynamic size, could be affected by the environmental conditions . For instance, the effective molecular size of the protein is different when it interacts with TiO 2 in differently charged systems . In the present study, the hydrodynamic sizes of Cyt c molecules at different ionic strengths were also determined based on the Stokes–Einstein equation (the size distribution is shown in Figure S7), as shown in Figure a.…”
Section: Resultsmentioning
confidence: 91%
“…Based on our previous work, we found that atomic force microscopy (AFM) can be used as an effective tool to reveal the mechanism at the molecular level. We have used AFM to quantify the molecular forces of one protein molecule with the TiO 2 surface under different complex and realistic conditions (surface roughness, 12 pH conditions, 33 heterogeneity, 34 etc. ), finding that these molecular forces depend both on the properties of the protein and the solid surface and the pH conditions but not the surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…46 Generally speaking, a strong interfacial protein network has its maximum amount of protein at the isoelectric point and high ionic strength due to attractive forces between the proteins or shielding of the inner protein charges, which result from a decrease of the effective Debye length. 47 At pH 7.4 which is close to the IEP, electrostatic protein-protein repulsions are low due to a minimum of the Debye length 48 and allow higher packing densities, leading to a maximized mass load. [49][50][51] Different heights of the films might indicate a more compact layer due to a denser packing of the mAb and less solvation at pH 7.4.…”
Section: Discussionmentioning
confidence: 99%